Nitrifiers Cooperate to Produce Nitrous Oxide in Plateau Wetland Sediments - Yuan, Dongdan; Zheng, Lei; Liu, Yong-Xin; Cheng, Hongguang; Ding, Aizhong; Wang, Xiaomin; Tan, Qiuyang; Wang, Xue; Xing, Yuzi; Xie, En; Wu, Haoming; Wang, Shanyun; et al. (2022)
The thawing of dormant plateau permafrost emits nitrous oxide (N2O) through wetlands; however, the N2O production mechanism in plateau wetlands is still unclear. Here, we used the 15N-18O double tracer technique and metagenomic sequencing to analyze the N2O production mechanism in the Yunnan-Kweichow and Qinghai-Tibet plateau wetlands during the summer of 2020. N2O production activity was detected in all 16 sediment samples (elevation 1020-4601 m: 2.55 +/- 0.42-26.38 +/- 3.25 ng N g-1 d-1) and was promoted by nitrifier denitrification (ND). The key functional genes of ND (amoA, hao, and nirK) belonged to complete ammonia oxidizing (comammox) bacteria, and the key ND species was the comammox bacterium Nitrospira nitrificans. We found that the comammox bacterial species N. nitrificans and the ammonia oxidizing bacterial (AOB) species Nitrosomonas europaea cooperate to produce N2O in the plateau wetland sediments. Furthermore, we inferred that environmental factors (elevation and total organic matter (TOM)) influence the cooperation pattern via N. nitrificans, thus affecting the N2O production activity in the plateau wetland sediments. Our findings advance the mechanistic understanding of nitrifiers in biogeochemical cycles and global climate change.